The Development of an Inclusive Social Science Based Contextual Interpretation Model: A New Approach to Address Contemporary Challenges in Quranic Studies - Fakhrurrozi, Ach; Rofiqi, Rofiqi; Gazali, Achmad (LPPPM STAI Darul Hikmah Bangkalan, 2024)
This research aims to develop a contextual interpretation model that connects Quranic studies with social sciences to ensure the Quran's relevance in addressing contemporary social challenges. This study employs a qualitative method using a library research model. The findings show that through an interdisciplinary approach, the integration of Quranic teachings with modern social, cultural, political, and economic realities can be achieved. This contextual interpretation approach emphasizes not only a literal understanding but also an analysis of the historical and social contexts surrounding the revelation. The study highlights the importance of the maqashidy approach, which focuses on the objectives of Sharia, as a framework for interpreting the Quran to ensure its teachings remain relevant to issues such as social justice, gender equality, and human rights. Furthermore, the findings indicate that the contextual interpretation model provides a more applicable and dynamic understanding of the Quran, ensuring that its messages remain relevant and can be applied in the lives of Muslims in the modern era.